Spectral characteristics of satellite links at ka band in the southern tropical region of India - Velaga, Sravya; Korrapati, Jagadeesh; Krishna B, Chaithanya; Matti, Vandana; Ch. Sri Kavya, K; K. Kotamraju, Sarat (International Journal of Engineering and Technology, 2017)
The objective of this study was to perform a spectral analysis of the Ka band propagation channel. Now a day, because of the expanding interest of the end users for multimedia services which require vast bandwidth, and because of the immersion of low frequency bands, for example, L, S, C bands, and Ku band in close future, satellite media transmission systems are moving to higher frequency bands. In such high frequency bands, the presence of the atmosphere strongly affects radiowave propagation and attenuation effects become so severe that system availability would not be sufficient if systems were designed in a conventional way with a static propagation margin.Â